Politeness Strategy Speaking Generation Z on Social Media Instagram Andi Meirling - Andi Meirling AJ; Rismayanti Rismayanti; Muhammad Ridha Anugrah Latief (Universitas Muria Kudus, 2026)
This study aims to explain the politeness strategies employed by netizens, particularly Generation Z, in the comment section of the Instagram account @azizahsalsha. Through this research, it is expected that language politeness as a cultural value is upheld in Indonesian society—especially in social media interactions on Instagram—can be better understood, including the linguistic markers of politeness, so that users become more cautious in expressing comments. This study adopts a qualitative research design with a pragmatic approach. The data consists of written texts collected through observation, documentation, transcription, and note-taking techniques. The observation method was applied by examining utterances captured through screenshots. The data were analyzed descriptively using the politeness theories proposed by Brown and Levinson and Watts. The findings indicate the use of direct strategies, positive politeness strategies, and negative politeness strategies. However, these strategies are predominantly realized through sarcastic word choices, resulting in a very low level of politeness, and in many cases, impolite language use among Generation Z. This study is significant in enhancing awareness of linguistic politeness literacy among Generation Z in digital interactions, particularly on Instagram . Keywords: Politeness strategies, Instagram, Generation Z